2010
DOI: 10.1016/j.jvs.2009.09.023
|View full text |Cite
|
Sign up to set email alerts
|

Delayed permanent paraplegia after endovascular repair of abdominal aortic aneurysm

Abstract: Spinal cord ischemia is a rare complication after abdominal aortic surgery and has been attributed to surgical devascularization of the spinal cord, atheroembolization of the cord circulation, or hypoperfusion of cord structures secondary to hypotension or cord edema. We present a diabetic, hypertensive 75-year-old male with endstage renal disease who presented with a 5.5 cm asymptomatic infrarenal abdominal aortic aneurysm, and concomitant 3.5 cm right common iliac artery aneurysm. After undergoing successful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…The present study also mentions the growing popularity of endovascular repair for treating not only Type A and Type B atheromatous lesions, as per the Trans-Atlantic Inter-Society Consensus II (TASC II) guidelines (Norgren et al, 2007a(Norgren et al, , 2007b, but also for the more extensive Type C and D lesions, alongside other techniques such as a combined hybrid endarterectomy (Piazza et al, 2011). However, despite this, there have also been many reports of paraplegia following endovascular repair (Reid et al, 2003;Kotelis et al, 2008;Goldstein et al, 2010).…”
mentioning
confidence: 58%
See 2 more Smart Citations
“…The present study also mentions the growing popularity of endovascular repair for treating not only Type A and Type B atheromatous lesions, as per the Trans-Atlantic Inter-Society Consensus II (TASC II) guidelines (Norgren et al, 2007a(Norgren et al, , 2007b, but also for the more extensive Type C and D lesions, alongside other techniques such as a combined hybrid endarterectomy (Piazza et al, 2011). However, despite this, there have also been many reports of paraplegia following endovascular repair (Reid et al, 2003;Kotelis et al, 2008;Goldstein et al, 2010).…”
mentioning
confidence: 58%
“…These include prolonged aortic cross-clamp time in open repairs (Svensson et al, 1994), reduced patent blood flow through an aortofemoral or femoral-femoral bypass graft (Goldstein et al, 2010), technical difficulties associated with emboli development following femoral cannulation in preparation for a bypass mechanism (O'Connor and Rothenberg, 1995) and systemic factors predisposing to hypotension such as sepsis. These include prolonged aortic cross-clamp time in open repairs (Svensson et al, 1994), reduced patent blood flow through an aortofemoral or femoral-femoral bypass graft (Goldstein et al, 2010), technical difficulties associated with emboli development following femoral cannulation in preparation for a bypass mechanism (O'Connor and Rothenberg, 1995) and systemic factors predisposing to hypotension such as sepsis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The authors reported that secondary hypotension might induce further reduction in spinal cord perfusion and contribute to the development of delayed paraplegia. 10) The precise pathophysiology in Case 3 could not be determined.…”
Section: Discussionmentioning
confidence: 99%
“…EVAR and open repair result in different mechanisms of SCI, including endovascular exclusion of vital arterial supply to the spinal cord, perioperative hypotensive episodes, and atheroembolization of debris into pelvic circulation following endovascular instrumentation 5,6,7. Three important mechanisms contribute to delayed SCI; reperfusion injury with the flux of inflammatory and neurochemical mediators, spinal cord edema, and lastly arterial hypotension 7,8,9. Recently, Awad et al unveiled the importance of spinal cord edema in the development of SCI, suggesting a multifactorial process of development 10.…”
Section: Discussionmentioning
confidence: 99%